Urinary bladder matrix scaffolds improve endometrial regeneration in a rat model of intrauterine adhesions. (23rd December 2019) - Zhang, Honghong; Zhang, Qing; Zhang, Jian; Sheng, Fei; Wu, Shuang; Yang, Fu; Li, Wen
Abstract : UBM contributes to endometrial regeneration and improves endometrium receptivity, and has the potential to become a new treatment for IUAs. Abstract : Intrauterine adhesions caused by damage to the basal layer of the endometrium have a serious impact on women's fertility. Currently, there is no effective treatment to promote the regeneration of the endometrium. Urinary bladder matrix (UBM) is a derivative extracellular matrix biomaterial that has a complete basement membrane and provides a basis for the body to achieve complete self-functional repair. In this study, UBM was transplanted into the uterine horns of intrauterine adhesions in Sprague-Dawley rats to test whether UBM could improve endometrial regeneration in rats with intrauterine adhesions. Thicker endometria, increased numbers of glands, fewer fibrotic areas and increased proliferation of cells and blood vessels were found in the UBM group compared to the injury group. Transplantation of UBM reduced the mRNA levels of proinflammatory cytokines (tumor necrosis factor α) and increased those of anti-inflammatory cytokines (basic fibroblast growth factor) compared to the injury group. In the UBM group, the mRNA expression of endometrial receptivity factors (leukemia inhibitory factor and integrin αVβ3 ) was higher than that in the injury group, but it was lower than that in the normal group and the sham-operated group. More embryos were seen in the UBM group than in the injury group, although the UBM group had fewer embryos than the normal and sham-operated groups. Therefore, UBM may contribute to endometrial regeneration and may improve endometrial receptivity and fertility.